CYTOTOXIC EFFECTS OF PROTEIN FRACTION ISOLATED FROM Curcuma mangga VAL RHIZOMES AND CONTAINING RIBOSOME-INACTIVATING PROTEINS ON CANCER CELL-LINES AND NORMAL CELL - Sismindari Sismindari; Retno S. Sudibyo; Endang Astuti (Indonesian Journal of Chemistry, 2010)
C. mangga Val. has been used as an alternative remedy for cancer in Yogyakarta. The protein fraction of C. mangga was identified to contain Ribosome-inactivating Protein which cleave supercoiled double stranded DNA in vitro. In this experiment, the protein fraction isolated from fresh, 400C dried and freeze dried C. mangga Val. rhizome was screened against HeLa, Raji cell-lines and normal mononuklear cells for cytotoxic effects. This would enable us to describe the sensitivity of the protein extract on different cell types. The level of cytotoxicity was determined on the level of LC50 which was based on the percentage of the cell death following the 24 hours incubation with the extract.